A novel plasma position and shape controller for advanced configuration development on the TCV tokamak. (22nd September 2017) - Anand, H.; Coda, S.; Felici, F.; Galperti, C.; Moret, J.-M.
Abstract: A novel plasma position and shape controller has been developed for the highly flexible shaping poloidal-field coil set of the TCV tokamak, to aid in the precise control of advanced configurations such as negative-triangularity plasmas, snowflake and super-X divertors, and doublets. This work follows and relies on the deployment of a new, sub-ms, real-time magnetic equilibrium-reconstruction algorithm. The controller formulation ensures flexibility through an ordering of controlled variables from the most easily to the least easily controlled, while respecting the hardware limits on the poloidal-field coil currents. A rigid, linearised plasma response model for the TCV tokamak is used for the verification and determination of the control parameters. The controller has been applied successfully to a variety of TCV plasma discharges.